2001
DOI: 10.1902/jop.2001.72.3.296
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Calcium Sulfate and Autogenous Bone Graft to Bioabsorbable Membranes Plus Autogenous Bone Graft in the Treatment of Intrabony Periodontal Defects: A Split‐Mouth Study

Abstract: Both therapies led to short-term improvement of the measured parameters; neither was superior to the other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 41 publications
3
57
1
1
Order By: Relevance
“…Therefore, a variety of approaches have been employed to improve the healing of bone defects. [4][5][6] Among them, autologous bone graft is considered to be the gold standard for bone implantation. 7) However, this procedure has limitations, which include restrictions in the amount of bone available to harvest and potential problems associated with the secondary wound.…”
mentioning
confidence: 99%
“…Therefore, a variety of approaches have been employed to improve the healing of bone defects. [4][5][6] Among them, autologous bone graft is considered to be the gold standard for bone implantation. 7) However, this procedure has limitations, which include restrictions in the amount of bone available to harvest and potential problems associated with the secondary wound.…”
mentioning
confidence: 99%
“…It is clear that higher amounts of Zn 21 and SO 4 22 ions are introduced into reaction medium using higher amounts of ZnSO 4 Á7H 2 O precursor. In this study, what seems that affects the mechanical strength of calcium sulfate cement is the lack or presence of SO 4 22 ions in the reaction medium. The mechanical strength of calcium sulfate cement comes from interlocking of gypsum crystals in the cement microstructure and can be influenced by the quantity and microstructural features of these crystals.…”
Section: Discussionmentioning
confidence: 85%
“…The mechanical strength of calcium sulfate cement comes from interlocking of gypsum crystals in the cement microstructure and can be influenced by the quantity and microstructural features of these crystals. The XRD and related quantitative analysis showed that higher amount of gypsum could be recrystallized in the calcium sulfate cements made with zinc sulfate solutions, regardless the concentration of SO 4 22 (or Zn 21 ). Thus, these cements had a higher compressive strength than the cement made with distilled water.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…When compared with Freeze dried bone allograft, a composite of Freeze dried allograft and autogenous grafts offered significantly improved results in osseous regeneration and pocket reduction, especially in combined one / 2 wall defects and furcation involvements [9]. Orsini in 2001 compared autologous bone plus calcium sulfate with autologous bone plus membrane and found neither treatment was superior to the other [10].…”
Section: A Results For Soft Tissue Parametersmentioning
confidence: 99%